Penerapan Akuntansi Lingkungan Berdasarkan Triple Bottom Line Pada Pt Teknindo Geosistem Unggul - Faradilla Mega Maharani; Achmad Maqsudi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine the application of environmental accounting in terms of the Triple Bottom Line theory. In this research the researcher used qualitative research by obtaining data through direct interviews at Pt Teknindo Geosistem Unggul. This research provides in-depth insight into the effectiveness of implementing triple bottom line-based environmental accounting in integrating critical aspects in existing environmental cost activities at Pt Teknindo Geosistem Unggul.